SWOT ANALYSIS OF ESG PRACTICES AMONG RURAL SUGARCANE PRODUCERS IN THE STATE OF SÃO PAULO - Fiori, Letícia de Almeida; dos Santos, Jeronimo Alves; Marjotta-Maistro, Marta Cristina (Seven Editora, 2026)
This article aimed to analyze Environmental, Social, and Corporate Governance (ESG) practices among sugarcane producers in the state of São Paulo, seeking to identify their potential impacts and challenges. Specifically, the SWOT methodology was applied to assess the relevance of ESG adoption, as well as to characterize the organizational environment, considering variables from both the general and task environment, in order to understand internal and external factors that influence its implementation. The research was based on bibliographic and documentary review, with emphasis on sustainability reports from companies in the sugar-energy sector, integrating discussions on agribusiness and corporate governance. The results indicated that, in the environmental dimension, strengths such as circular economy and the use of clean technologies prevail, while weaknesses remain related to the use of fossil fuels and waste management. In the social dimension, progress was observed in inclusion and community projects, although gaps persist in equity and the participation of small producers. In the governance dimension, certifications and compliance structures stand out, contrasting with limitations in cybersecurity and the difficulties of independent producers to adhere. It is concluded that the effective incorporation of ESG strengthens the sustainability and competitiveness of the sector, provided it is accompanied by innovation, capacity building, and integrated management strategies. It should be noted as a limitation the dependence on secondary sources, especially reports from mills, which may reduce the representativeness of small and medium-sized producers.